La idea de justicia en la resolución de conflictos en la Central Única Distrital de la Ronda Campesina de Acora - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2018)
The value of this work is to show from the direct and real task, not from theory or regulations, the dynamics of a communal Justice, with the activities carried out by the ronderos, and that we are sure, will swell the already enough works that are being developed around legal pluralism from the side of the southern Peruvian highlands, in order to promote in a short time in the future that we can have in our country the coexistence of recognized and protected legal systems and orders, through a state that is also plural and intercultural that can finally be congruent with the type of society and cultures that we have in Peru.